ANALISIS DAN PERANCANGAN SISTEM INFORMASI PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG BERGERAK DI BIDANG PLASTIK - PRADIPTA WARGONO, CHRISTIAN (: 2303-1719)
PT Multiplast Indojaya is a manufacturing company engaged in the manufacture of objects made of plastic material. PT Multiplast Indojaya have difficulty in the recording inventory because during the using manual system in the process of purchasing raw materials, supporting materials, and manufacturing to production expenses to be sent to the distributor. The use of a manual system on PT Multiplast Indojaya was in adequate because the resulting information is often inaccurate and requires much time and effort to obtain the desired information. Therefore, the purpose of this study was to analyze for weaknesses in the existing system and to design the system inventory in PT Multiplast Indojaya and control the purchase of raw or support materials, production processes and finished goods spending. This study is a descriptive study with qualitative data types with data from internal company sources. Design inventory system information PT Multiplast indojaya include systems analysis, conceptual design phase of physical design. The results of this study produced an analysis of the conceptual design of a data flow diagram and ERD data modeling and physical design and physical form of the design output. The study is expected to address solving the problems inventory system that existed at the company.